The Energy Efficiency Plan of the University of a Coruña: a Commitment to Photovoltaic Solar Energy in The Face of The Challenge of Renewable Energies - Amparo, Casares-Gallego; Antonio, Raya de Blas; Jesús, Giz Novo; Bernardo, Lage Arias; Domingo, Calvo Dopico (Journal of Sustainability Perspectives, 2023)
Since 2020, the University of a Coruña (UDC) has been developing an Energy Efficiency Plan that is already yielding its first beneficial results. An ambitious plan to renovate the building envelopes to make them thermally efficient, together with a determined policy of centralization in district heating and a commitment to photovoltaic solar energy on the roofs, constitute the essence of this Energy Efficiency Plan. The renewal of aerothermal heat pump systems, at the limit of their useful life, and the replacement of diesel boilers with aerothermal or gas boilers, which are more efficient and require less maintenance, is another major challenge. The climatic peculiarity of our area, a temperate oceanic climate with cool summers, allows the use of free cooling throughout the year with high performance. The widespread changeover of lighting to LED technology has been a determining factor in energy savings. We raise two fundamental questions to be determined for the proposed model plan: what indicators can we establish as efficient performance and what capacity does the model plan have to maintain its efficiency in another location.